Applying mathematical modelling to estimate the impact of COVID-19-related VMMC service disruptions on new HIV infections in Zimbabwe - Newton Chagoma; Tiwonge Kanyenda; Bothwell Pindiwe; Howard Nyika; Lawrence Nyazema; John Stover; Danielle Resar; Natsai Shoko; Sarah Jenkins; Yemurai Katanda; Sinokuthemba Xaba; Owen Mugurungi (BMC Infectious Diseases, 2023)
Abstract Background The COVID-19 pandemic has overwhelmed health systems with knock on effects on diagnosis, treatment, and care. To mitigate the impact, the government of Zimbabwe enforced a strict lockdown beginning 30 March 2020 which ran intermittently until early 2021. In this period, the Ministry of Health and Childcare strategically prioritized delivery of services leading to partial and full suspension of services considered non-essential, including HIV prevention. As a result, Voluntary Medical Male Circumcision (VMMC) services were disrupted leading to an 80% decline in circumcisions conducted in 2020. Given the efficacy of VMMC, we quantified the potential effects of VMMC service disruption on new HIV infections in Zimbabwe. Methods We applied the GOALS model to evaluate the impact of COVID-19-related disruptions on reducing new HIV infections over 30-years. GOALS is an HIV simulation model that estimates number of new HIV infections based on sexual behaviours of population groups. The model is parameterized based on national surveys and HIV program data. We hypothesized three coverage scenarios by 2030: scenario I - pre-COVID trajectory: 80% VMMC coverage; Scenario II - marginal COVID-19 impact: 60% VMMC coverage, and scenario III - severe COVID-19 impact: 45% VMMC coverage. VMMC coverage between 2020 and 2030 was linearly interpolated to attain the estimated coverage and then held constant from 2030 to 2050, and discounted outcomes at 3%. Results Compared to the baseline scenario I, in scenario II, we estimated that the disruption of VMMC services would generate an average of 200 (176–224) additional new infections per year and 7,200 new HIV infections over the next 30 years. For scenario III, we estimated an average of 413 (389–437) additional new HIV infections per year and 15,000 new HIV infections over the next 30 years. The disruption of VMMC services could generate additional future HIV treatment costs ranging from $27 million to $55 million dollars across scenarios II and III, respectively. Conclusion COVID-19 disruptions destabilized delivery of VMMC services which could contribute to an additional 7,200 new infections over the next 30 years. Unless mitigated, these disruptions could derail the national goals of reducing new infections by 2030.